Peter Hacker on forms of representation: A critical evaluation. - Yan, Hektor K. T. (Philosophical Investigations, 2023)
P. M. S. Hacker's tetralogy on human nature (2007–2021) is a recent contribution to philosophical anthropology. In this work, the expression 'form of representation' appears at crucial points of discussion. This paper begins with an exposition and analysis of this notion, followed by a look at how it is utilised in the discussion of knowledge, the mind, and other emotive and moral concepts. It then turns to a comparison of 'forms of representation' with two important concepts, namely, analogy and metaphor. To offer an evaluation of 'forms of representation' as a critical tool, this paper examines the increasingly common tendency for humans to identify with their brains.